Curbing Tax Evasion through Taxpayer Identification Number (TIN) in Niger State, Nigeria - Hassan Abdul; Bilkisu Abubakar; Umaru Zubairu (Faculty of Economics, Universitas Sriwijaya, 2021)
This study assessed the effectiveness of the introduction of Taxpayer Identification Number (TIN) in curbing tax evasion in Niger State, Nigeria from the point of view of ten tax officers of the Niger State Internal Revenue Service. Adopting a qualitative research design, ten tax officers were interviewed to understand their collective perceptions of the level of tax evasion in Niger State before and after the introduction of TIN. Thematic analyses of the interviews revealed that all ten tax officials agreed that tax evasion was at a very high level before the introduction of TIN, but reduced dramatically after the introduction of TIN proving its efficacy. The study recommended that tax evasion in the State could be further reduced if businesses operating in the informal sector could be registered and included in the database of taxable entities.